Aspiracje zawodowe rodzeństwa pełnosprawnego podyktowane doświadczeniem niepełnosprawności w rodzinie - Żyta, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
This article shows the impact of having a sibling with disabilities in the profession and career choices. Growing up with a brother or sister with a disability affects the development of personality traits and may be associated with the choice of professions related to helping people. This article presents a review of the literature devoted to this issue.